Laccase-1 in the pea aphid, Acyrthosiphon pisum (Harris) - Liang, Qixin (Kansas State University, 2006)
Laccases belong to the “multicopper oxidase” family of proteins, and can oxidize o-diphenols and p-diphenols in the presence of molecular oxygen. Laccases have been well characterized in wood-rotting fungi where they appear to play a role in lignin degradation, morphogenesis, and stress defense. More recently, laccase-2 has been found to play a role in the insect cuticle sclerotization and tanning. In addition, it has been hypothesized that laccase-1 may be involved in the oxidation of toxic phenolic compounds ingested by insects during feeding. A laccase-type phenoloxidase has been identified in the pea aphid, Acyrthosiphon pisum (Harris) using a combination of substrates that react with laccase. Within the pea aphid, laccase-1 transcript was found to be localized within the gut and the salivary glands. Finally, the specific regions where laccase-1 was present in the salivary gland was visualized using immunohistochemistry.
Keywords: Laccase; Aphid; Salivary; phenoloxidase